PENGARUH MOTIVASI, INSENTIF DAN IKLIM KERJA TERHADAP KINERJA KARYAWAN PRODUKSI PT. CIPTA TPI (MNCTV) - Agung Raharjo; Kaman Nainggolan (Jurnal Komunikasi, 2017)
The company which is ready to compete must have effective management. In addition to motivation, to improve the performance of employees in effective management requires the support of employees who are qualified and competent in their fields. On the other hand the employees construction must take precedence as the main asset of the company. The learning process should be a corporate culture so that the skills of the employees can be maintained, even improved. Based on the above description, the writer proposed a study entitled “The Influence of Motivation, Incentives and Work Climate towards The Production Work Performance PT. Cipta TPI (MNCTV)”. The method of this research is done against data obtained from the questionnaire answers and the results used to analyze data in the form of figures and calculations with statistical methods. Such data should be classified in a particular category by using specific tables to make it easier to analyze. For it to be used SPSS Analysis program. This research proved a boost of motivation and incentives is very influential on work performance of the employees in the Office of PT. Cipta TPI (MNCTV), then to improve the performance of employees, the main thing to note are the motivation, incentives and a comfortable work climate and bolster employee productivity.Keywords: Motivation, Incentives, Work Climate, Employee.